Studi Komparatif Penyelesaian Sengketa Lingkungan Di Pengadilan Tata Usaha Negara Indonesia Dan Thailand - Francisca Romana Harjiyatni; Meicke Caroline Anthony (Fakultas Hukum Universitas Islam Indonesia, 2022)
This study aims to analyze the comparison of environmental dispute resolution in the State Administrative Court (PTUN) of Indonesia and its Thailand equivalent. This is a normative legal research, using statutory and comparative approaches. The results of the study are presented in an analytical descriptive form. The results of the study conclude that first, the equatlisation for the settlement of environmental disputes in the Indonesian PTUN and the ones in Thailand is based on the General Administrative Court Procedure Law as regulated in the laws governing the PTUN of each country, but technical guidelines for resolving environmental disputes in the PTUN are issued by the respective Supreme Courts of each country. Second, the first difference is that the Thai Administrative Court provides special arrangements related to compensation issues which include costs for health problems, costs for damage to natural resources, loss of identity and community arts and culture. Meanwhile, the PTUN Indonesia provides very limited compensation and prioritizes the claim for the validity of the object of dispute. The second difference is that the handling of environmental problems in the Thai Administrative Court examines the substance and facts related to the environment more deeply, so that a real picture of environmental problems is obtained in the field. An in-depth study of the substance, facts, environmental problems in the field is taken into consideration by the judge in making a decision, even though administratively there are no problems. Meanwhile, the dispute resolution in the Indonesian PTUN is administrative and procedural in nature. Key Words: Environmental dispute; state administrative court; environment Abstrak Penelitian ini bertujuan untuk menganalisis perbandingan penyelesaian sengketa lingkungan di Pengadilan Tata Usaha Negara (PTUN) Indonesia dan Thailand. Penelitian ini merupakan penelitian hukum normatif, dengan menggunakan pendekatan perundang-undangan dan komparasi. Hasil penelitian disajikan dalam bentuk deskriptif analitis. Hasil Penelitian menyimpulkan, pertama, persamaan penyelesaian sengketa lingkungan di PTUN Indonesia maupun Thailand berdasarkan Hukum Acara PTUN pada umumnya seperti yang diatur dalam Undang-Undang yang mengatur mengenai PTUN masing-masing negara, namun pedoman teknis penyelesaian sengketa lingkungan di PTUN diterbitkan oleh Mahkamah Agung masing-masing. Kedua, perbedaan pertama adalah bahwa di PTUN Thailand memberikan pengaturan khusus terkait dengan masalah ganti rugi yang mencakup biaya gangguan kesehatan, biaya kerusakan sumber daya alam, hilang identitas dan seni budaya masyarakat. Sedangkan PTUN Indonesia memberikan ganti rugi yang sangat terbatas dan lebih mengutamakan mengenai tuntutan keabsahan obyek sengketa. Perbedaan kedua adalah penanganan masalah lingkungan di Pengadilan Administrasi Thailand memeriksa substansi dan fakta-fakta yang berkaitan dengan lingkungan lebih mendalam, sehingga diperoleh gambaran permasalahan lingkungan secara nyata di lapangan. Kajian yang mendalam tentang substansi, fakta-fakta, permasalahan lingkungan di lapangan dijadikan pertimbangan hakim dalam memutus, meskipun secara administrasi tidak ada masalah. Sedangkan penyelesaian sengketa di PTUN Indonesia bersifat administratif dan formal prosedural. Kata Kunci: Sengketa lingkungan; peradilan tata usaha negara; lingkungan hidup